Medical Foods from Natural Sources - Kaur, Meera (Springer, 2017)
To date, most published books on enteral nutrition support focus only on issues such as the rationale, specific nutrient requirements for various disease conditions, and practical approaches to the delivery, monitoring, and complications preventions while providing enteral nutrition support. None offer information relating to the developmental aspects of enteral foods, e.g. processing technology, types of ingredients, physicochemical and nutritional characteristics, shelf life evaluations, etc. These aspects are critical because they affect the overall acceptability, tolerance, and effectiveness of enteral nutrition support.